2019
DOI: 10.2478/raon-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perioperative treatment on survival of resectable gastric cancer patients after D2 lymphadenectomy: a single European centre propensity score matching analysis

Abstract: Background To determine the effects of perioperative treatment of gastric cancer patients, we conducted an analysis with propensity score matched patient groups to determine the role of perioperative chemotherapy in patients after D2 lymphadenectomy. Patients and methods From our database of 1563 patients, 482 patients were selected with propensity score matching and divided into two balanced groups: 241 patients in the surgery only group and 241 patients in the perioperative group. The long-term results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A Dutch trial demonstrated that GC patients with N2 stage, who underwent D2 dissection, had a survival benefit superior to those who underwent D1 dissection [10]. Furthermore, the survival benefit for perioperative treatment in the TNM stages T3, N2 and N3b patients after D2 lymphadenectomy is affirmed again by Jagric et al [24]. In addition, the application of preoperative NAC in GC patients has drawn increased attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Dutch trial demonstrated that GC patients with N2 stage, who underwent D2 dissection, had a survival benefit superior to those who underwent D1 dissection [10]. Furthermore, the survival benefit for perioperative treatment in the TNM stages T3, N2 and N3b patients after D2 lymphadenectomy is affirmed again by Jagric et al [24]. In addition, the application of preoperative NAC in GC patients has drawn increased attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the survival benefit for perioperative treatment in the TNM stages T3, N2 and N3b patients after D2 lymphadenectomy is affirmed again by Jagric et al . [24]. In addition, the application of preoperative NAC in GC patients has drawn increased attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The regimen used for perioperative treatment was 5-FU–leucovorin–oxaliplatin–docetaxel (FLOT) four cycles pre- and four cycles post-operative. The precise doses for the regiment are provided in the as described elsewhere [ 9 , 10 ]. The inclusion criteria for this study were adenocarcinoma diagnosed between 2015 and 2022, UICC tumor stages 0-IV, and complete follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Severe renal impairment (calculated creatinine clearance less than 30 mL/min) suspected dihydro pyrimidine dehydrogenase (DPD) de ciency. Perioperative treatment was administered as described elsewhere [10]. All patient characteristics, operations, and tumor characteristics were prospectively stored in the hospital database.…”
Section: Patientsmentioning
confidence: 99%